Pengembangan Aplikasi Belajar Akhlak Siswa Sebagai Upaya Penguatan Pendidikan Karakter Peserta Didik Sekolah Dasar - Utari Akhir Gusti; Habi Akbar; Rismawati Rismawati; Aulia Rama Putri; Dilla Sintya (PAKAR Pendidikan, 2023)
The development of technology in the world of educationencourages the educational process to be more advanced and flexible. The introduction of technology to students aims to make them have extensive knowledge and experience to be used in their lives in the future. Kuriculum 2013 emphasizes the panyof intellectual, emotional, and spiritual intelligence. In its implementation, there are still few learning media available that can increase spiritual intelligence. So far, learning media has only been aimed at intellectual and emotional intelligence, even though spiritual intelligence has an important role in building the character of students. Therefore, it is necessary to develop learning media that can increasethe 3 intelligences, especially spiritual intelligence. The Student Learning Application (BAS) is an application that is integrated with moral strengthening in students. The type of research used is Research and development with 4D models (define, design, develop, and dissminate). In this study, it only reached the stage of developing with validity testing and small-scale testing. Thedata analysis techniques are qualitative and quantitative. The research was conducted at SDN 18 Air Tawar Timur, SDN 25 Air Tawar Timur, and SD Pembangunan Universitas Negeri Padang. Data collection techniques are carried out by observation, interviews, distributing product validation questionnaires, and response test questionnaires to students and elementary school teachers. The results of the study obtained results that the media was valid and the response test obtained quite good results. This learning media can be used as an alternative in an effort to strengthen spiritual values in learning media in schools.